Thromboembolic prevention in athletes: management of anticoagulation in sports players affected by atrial fibrillation - Minardi, Simona; Sciarra, Luigi; Robles, Antonio Gianluca; Scara, Antonio; Sciarra, Francesco; De Masi De Luca, Gabriele; Romano, Silvio (Frontiers in Pharmacology, 2024)
Atrial fibrillation (AF) is a common cardiac arrhythmia that poses a significant risk of stroke and thromboembolic events. Anticoagulation therapy is essential for preventing stroke in patients with AF.An increasing number of people of all ages, including cardiac patients, approach physical activity as both a leisure-time exercise and a competitive sport. Therefore, patients at risk of AF are increasingly allowed to practice sports activities. Management of oral anticoagulant therapy (OAT) in these patients is extremely challenging because of the need to balance the risks and benefits of medications, considering both haemorrhagic (in case of trauma) and ischaemic complications in when the drugs are avoided. Official recommendations are limited for these patients and forbid sports that increase the risk of trauma and consequent bleeding in most cases. These recommendations have been strongly influenced by the "traditional" management of OAT, which mainly involves coumarin derivatives.Non-vitamin K antagonist direct oral anticoagulants (DOACs), with their more favourable pharmacokinetic-pharmacodynamic profile than that of coumarin derivatives, may represent an opportunity to modify the approach to sports activity in patients with AF and indications for OAT. This study aimed to review the use of anticoagulants in athletes with AF, highlight their efficacy and safety, and provide practical considerations regarding their management.